COVID-19 Clinical Trial Oversight at a Major Academic Medical Center: Approach of the Michigan Medicine COVID-19 Clinical Trial Committees - Spector-Bagdady, Kayte (Clin Infect Dis, 2020)
Clinicians – eager to offer the best care in the absence of guiding data – have provided patients with COVID-19 diverse clinical interventions. This usage has led to perceptions of efficacy of some interventions that, while receiving media coverage, lack robust evidence. Moving forward, randomized controlled clinical trials (RCTs) are necessary to ensure that clinicians can treat patients effectively during this outbreak and the next. To do so, academic medical centers must address two key research issues: (1) how to effectively and efficiently determine which trials have the best chance of benefiting current and future patients, and (2) how to establish a transparent and ethical process for subject recruitment while maintaining research integrity and without overburdening patients or staff. We share here the current methods used by the University of Michigan to address these issues.